2006
DOI: 10.1783/147118906778586480
|View full text |Cite
|
Sign up to set email alerts
|

Quality of delivery of the Standard Days Method as compared with contraceptive pills in Rwanda

Abstract: Background and methodology Replicating a Peruvian study, this research introduced the Standard Days Method (SDM) into Rwanda Ministry of Health clinics and evaluated client counselling on the new method against that given for contraceptive pills. Providers received technical reinforcement concerning established methods in addition to SDM training. To evaluate their quality of care, simulated clients implemented a service test in visits to 20 clinics.Results As in Peru, providers exchanged significantly more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In most studies, SDM was offered as part of the standard FP and reproductive health (RH) service delivery in the study site catchment area: In 10 studies, SDM was offered alone, and in other studies it was compared to condoms, injectables, sterilization, Depo-Provera (DMPA), and pills (Arévalo et al 2010b;Dosajh, Ghosh and Lundgren 2006;Gribble et al 2008;Johri, Panwar and Lundgren 2005;Kavle, Eber and Lundgren 2012;León et al 2006;León et al 2007a;Lundgren et al 2005;Mohammadpourasl 2007;Ram and Doracaj N.D.;Rosen, Winfrey and Adesina 2013). The typical population in SDM studies comprised women of reproductive age who use SDM; some studies included comparisons of SDM users to non-users.…”
Section: Figure 1 Sdm Studies In India Bymentioning
confidence: 99%
See 2 more Smart Citations
“…In most studies, SDM was offered as part of the standard FP and reproductive health (RH) service delivery in the study site catchment area: In 10 studies, SDM was offered alone, and in other studies it was compared to condoms, injectables, sterilization, Depo-Provera (DMPA), and pills (Arévalo et al 2010b;Dosajh, Ghosh and Lundgren 2006;Gribble et al 2008;Johri, Panwar and Lundgren 2005;Kavle, Eber and Lundgren 2012;León et al 2006;León et al 2007a;Lundgren et al 2005;Mohammadpourasl 2007;Ram and Doracaj N.D.;Rosen, Winfrey and Adesina 2013). The typical population in SDM studies comprised women of reproductive age who use SDM; some studies included comparisons of SDM users to non-users.…”
Section: Figure 1 Sdm Studies In India Bymentioning
confidence: 99%
“…Comments from providers also reflected dissatisfaction with the restrictions of the eligibility criteria (i.e. cycle length requirement), and some providers refused to provide the method unless acceptors' partners participated in the consultation (20% of providers in Rwanda would not provide SDM without the partner present) (Blair et al 2007, León et al 2006. Additionally, some providers expressed concerns about SDM's effectiveness, which underscores the need to emphasize the evidence base during provider training (Kavle et al 2009).…”
Section: Outcomes For Providersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some of the providers had complained that the SDM necessitated time-consuming counselling sessions. Studies conducted in India (SDM 10 minutes vs Pill 8 minutes),17 Rwanda (SDM 44 minutes vs Pill 38 minutes)18 and Peru (SDM 23 minutes vs Pill 15 minutes)19 demonstrated that the SDM can be offered with a similar length counselling session as required for the oral contraceptive pill. The amount of time needed to counsel new SDM users typically did not exceed what is generally allocated in respect of new family planning consultations 10.…”
Section: Discussionmentioning
confidence: 99%
“…This test consists of a client script that depicts a contraceptive history, conjugal circumstances, method preferences, and other client characteristics; a trained simulated client who pretends to be the woman of the script as she requests services and responds to questions from a provider who believes she is attending a real client, and an observation checklist in a Yes-No format that the simulated client completes upon exiting the clinic. (For details, see León et al, 2001León et al, , 2006León, Brambila, et al, 2005;León, Ríos, et al, 2005. ) In the service test, item responses pertaining to the expected provider behaviors are scored 1 (observed) or 0 (not observed), and the item scores are summated or averaged to generate indicator scores.…”
Section: Measurement Toolmentioning
confidence: 99%